Engineered Functional Recovery of Microbial Rhodopsin Without Retinal‐Binding Lysine. (2nd July 2019) - Yamauchi, Yumeka; Konno, Masae; Yamada, Daichi; Yura, Kei; Inoue, Keiichi; Béjà, Oded; Kandori, Hideki
Abstract: Definition of rhodopsin is the retinal‐binding membrane protein with the Schiff base linkage at a lysine on the 7 th transmembrane helix. However, ~ 600 microbial rhodopsins lack retinal‐binding lysine at the corresponding position (Rh‐noK) among ~ 5500 known microbial rhodopsins, suggesting that Rh‐noK has each functional role without chromophore. Here, we report successful functional recovery of Rh‐noK. Two Rh‐noKs from bacteria were heterologously expressed in Escherichia coli, which exhibited no color. When retinal‐binding lysine was introduced, one of them gained visible color. Additional mutation of the Schiff base counterion further gained proton‐pumping activity. Successful engineered functional recovery such as visible color and proton‐pump activity suggests that the Rh‐noK protein forms a characteristic structure of microbial rhodopsins. Abstract : Definition of rhodopsin is the retinal‐binding membrane protein with the Schiff base linkage at a lysine on the 7 th transmembrane helix. However, more than 10% of known microbial rhodopsins lack retinal‐binding lysine at the corresponding position (Rh‐noK), suggesting their functional roles. We expressed two Rh‐noKs from bacteria heterologously in Escherichia coli, which exhibited no color. When retinal‐binding lysine was introduced, one of them gained visible color. Additional mutation of the Schiff base counterion further gained proton‐pumping activity. Successful engineered functional recovery such as visible color and proton‐pump activity suggests that the Rh‐noK protein forms a characteristic structure of microbial rhodopsins.